If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(h + 9) + -1h = h + 16 Reorder the terms: 2(9 + h) + -1h = h + 16 (9 * 2 + h * 2) + -1h = h + 16 (18 + 2h) + -1h = h + 16 Combine like terms: 2h + -1h = 1h 18 + 1h = h + 16 Reorder the terms: 18 + 1h = 16 + h Solving 18 + 1h = 16 + h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-1h' to each side of the equation. 18 + 1h + -1h = 16 + h + -1h Combine like terms: 1h + -1h = 0 18 + 0 = 16 + h + -1h 18 = 16 + h + -1h Combine like terms: h + -1h = 0 18 = 16 + 0 18 = 16 Add '-18' to each side of the equation. 18 + -18 = 16 + -18 Combine like terms: 18 + -18 = 0 0 = 16 + -18 Combine like terms: 16 + -18 = -2 0 = -2 Simplifying 0 = -2 Combine like terms: 0 + 2 = 2 2 = -2 + 2 Combine like terms: -2 + 2 = 0 2 = 0 The solution to this equation could not be determined.
| y-5=-1+7 | | 3x+12x-6=3(5x+7) | | x-1/8=15/8 | | 16-2t=3t+9 | | x-1/8=15/8= | | 12a-17=9 | | -2p=9 | | -10w+1=25 | | 4x+y-2=16 | | 81-y+6y+4+8y-18=180 | | -4(5x-12)= | | 2k-12=4 | | 22.5=3y | | 2x+1-3x-5= | | 24x+19=3(6x+8)+6x-5 | | 7g+14=8g+5 | | 4x+3=4y+1 | | .3x-1.6=.5 | | 4x+3=4y-1 | | 1-6x=8-7-3x | | 27x^2-75x+28=0 | | 9(2x-9.5)=-16.5x+8x | | 25=-5/6y | | 122/3/2 | | -6.47-16.4g=7.53-12.4g | | 4.99-10.9t=-1.17+4.5 | | 25x-30=370 | | 15+8y=47 | | -2.6b-1=18.25-1.5b | | -4.3g=-2.7g+17.6 | | 4x+20x-9=6(4x+6) | | 10=-x-2y |